Bioprospecting Antiproliferative Marine Microbiota From Submarine Volcano Tagoro - García-Davis, Sara; Reyes, Carolina P.; Lagunes, Irene; Padrón, José M.; Fraile-Nuez, Eugenio; Fernández, José J.; Díaz-Marrero, Ana R. (Frontiers in Marine Science, 2021)
Marine ecosystems are unique and rich reservoirs of biodiversity with high potential towards improving the quality of human life. The extreme physical-chemical conditions of the oceans have favored marine organisms to produce a great variety of new molecules as a mechanism to ensure their survival, and such compounds possess great biopharmaceutical interest. In particular, marine microbiota represent a promising and inexhaustible source for the development of new drugs. This work presents the taxonomic study of the samples obtained from the underwater volcano Tagoro, which has allowed us to develop a collection of 182 marine bacterial strains. On October 10th, 2011, at La Restinga–El Mar de Las Calmas Marine Reserve, an underwater eruption gave rise to a novel shallow submarine volcano at 1.8 km south of the island of El Hierro, Canary Islands, Spain. During the first six months, extreme physical–chemical perturbations, comprising thermal changes, water acidification, deoxygenation, and metal enrichment, resulted in significant alterations of the marine ecosystem. After March 2012, the submarine volcano Tagoro entered an active hydrothermal phase that involved a release of heat, gases, metals and micronutrients that continues till our present. During 2016, our research team had the opportunity to participate in one of the monitoring oceanographic cruises carried out in the area in order to isolate microorganisms associated with both rock samples and deep-sea invertebrates over Tagoro submarine volcano. In this study, Proteobacteria revealed as the most abundant Phylum with 70.2% among all isolated strains, followed by Firmicutes 19%, Actinobacteria 9.5% and Bacteroidetes 1.2%. Furthermore, we present the results of the antiproliferative assays of the extracts obtained from small-scale cultures of selected bacterial strains. An analysis of the effects of culture conditions in the antiproliferative activity showed that strains grown in Marine Broth (MB) presented lower GI50 values than those cultured in a modified medium (MM1). This effect is improved when the strains are incubated under agitation conditions. The antiproliferative potential of genera such as Halobacillus, Kangiella, Photobacterium and Halomonas is revealed. Their biotechnological development provides an excellent starting point to access novel secondary metabolites and enzymes with potential for pharmaceutical and industrial applications.